Computer Engineering and Technology 17th CCF Conference, NCCET 2013, Xining, China, July 20-22, 2013. Revised Selected Papers - Xu, Weixia.; Xiao, Liquan.; Zhang, Chengyi.; Li, Jinwen.; Yu, Liyan. (Communications in Computer and Information Science, 2013)
This book constitutes the refereed proceedings of the 17th National Conference on Computer Engineering and Technology, NCCET 2013, held in Xining, China, in July 2013. The 26 papers presented were carefully reviewed and selected from 234 submissions. They are organized in topical sections named: Application Specific Processors; Communication Architecture; Computer Application and Software Optimization; IC Design and Test; Processor Architecture; Technology on the Horizon.